2022
DOI: 10.18843/ijcms/v13i3/01
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Model of Continuance Intention toward Mobile Wallet Services in India

Abstract: Purpose: A significant increase in smartphone adoption in India has resulted in consumers availing various services through it. Due to the affordable rates of mobile internet, coupled with various other factors, the demand for mobile wallet services for instance, has surged in the past few years, increasing competition. This study aims to investigate some of the important determinants of continuance intention of mobile wallet customers in India. Methodology: We collected 325 responses through an online survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…Research conducted by Brahanta & Wardhani (2021) in Indonesia found that perceived ease of use has a significant effect on continuance intention. Research by Chaveesuk et al (2022) in Thailand and Saibaba (2022) in India also showed similar results. Based on study theory And study empirical then the hypothesis can be formulated as follows:…”
Section: Perceived Ease Of Use and Continuance Intentionsupporting
confidence: 62%
See 3 more Smart Citations
“…Research conducted by Brahanta & Wardhani (2021) in Indonesia found that perceived ease of use has a significant effect on continuance intention. Research by Chaveesuk et al (2022) in Thailand and Saibaba (2022) in India also showed similar results. Based on study theory And study empirical then the hypothesis can be formulated as follows:…”
Section: Perceived Ease Of Use and Continuance Intentionsupporting
confidence: 62%
“…Based on Technology Continuance Theory (Liao et al, 2009), perceived usefulness has implications for continuance intention. Previous studies have shown that perceived usefulness has a significant effect on continuance intention (Daragmeh et al, 2021;Foroughi et al, 2019;Garrouch, 2021;Saibaba, 2022). The results of Daragmeh et al (2021) in Hungary proves that perceived usefulness has a significant effect on continuance intention.…”
Section: Perceived Usefulness and Continuance Intentionmentioning
confidence: 62%
See 2 more Smart Citations